Konsep Kearifan Lokal Kurikulum Berbasis Cinta pada Madrasah Ibtidaiyah - Ahmad Padila Selamet; M.Ali Akbar; Ahmad Zainuri; Frika Fatimah Zahra (Aliansi: Jurnal Hukum, Pendidikan dan Sosial Humaniora, 2025)
This article aims to explore the application of local wisdom values ​​in the Love-Based Curriculum at Islamic Elementary Schools (MI) as a strategy for building character, strengthening cultural identity, and strengthening humanity-oriented education. The Love-Based Curriculum focuses on the values ​​of compassion, empathy, social responsibility, and respect for diversity, which are integrated into all subject areas. The integration of cultural and local elements serves to increase the connection between education and the realities of students' lives. This study is compiled based on research findings regarding the implementation of the Love Curriculum at MI Al-Islah Palembang and research related to local wisdom-based learning at Islamic Elementary Schools. The results of the analysis indicate that the application of love values ​​and local wisdom makes a positive contribution to character formation, increasing learning motivation, and strengthening students' cultural identity. The main challenges lie in the limited availability of learning tools, the need for teacher training, and adequate policy support.